Pemberdayaan Masyarakat melalui Pemanfaatan Gonggong sebagai Produk Kerajinan Gantungan Kunci di Rempang Eco City - Leony Puspita Dewanti; Rasti Antika; Anita Taruli Silitonga; Ellis Supri Yanni; Joey Riche Orion; Jens Jeremias Sinaga; Merinda Sitanggang; Solvian Putri Halawa; Syafiq Ramadhan; Siti Revi Rahmadani; Jumsurizal Jumsurizal (Pusat Riset dan Inovasi Nasional, 2026)
This community service activity, carried out by KKN Group 62 Rempang Eco City, Senbulang, Universitas Maritim Raja Ali Haji, aims to enhance the skills and economic value of coastal communities through the utilization of gonggong shells (Strombus sp.) as raw materials for handicrafts. Gonggong is widely known as a food source, while its shells remain underutilized and are often discarded as waste. The program was implemented through a training activity on making keychains from gonggong shells in Rempang Eco City. The methods included socialization, demonstration, and hands-on practice accompanied by guidance from the facilitators. The results show that participants improved their ability to process gonggong shells into simple craft products with potential market value. Although the activity was still limited to initial production and did not yet cover marketing, it successfully provided new insights and opened opportunities for creative entrepreneurship within the community. With further assistance and development, gonggong shell utilization is expected to evolve into a sustainable handicraft business that contributes to the economic welfare of coastal communities.